Characterization of African Equatorial Ionization Anomaly During the Maximum Phase of Solar Cycle 24. Issue 9 (28th August 2020) - Oyedokun, O. J.; Akala, A. O.; Oyeyemi, E. O.
Abstract: This study characterizes the African equatorial ionization anomaly (EIA) during the maximum phase of Solar Cycle 24 (2012–2015). Total electron content (TEC) data were obtained from a chain of 13 African Global Navigation Satellite System (GNSS) receivers (within 36–42°E geographic longitude; 29°N to 10°S geographic latitude; ±20°N magnetic latitude) to study quiet time variations of TEC and thereafter construct the EIA profiles. The correlations of TEC for pairs of conjugate stations within the African EIA were determined. TEC station‐to‐trough ratio (TEC‐STR) was used as an index to determine the strength of the EIA crests. Furthermore, the variability of the EIA crests on a 3‐hourly basis over each month was investigated. Overall, equinoxes recorded the highest values of TEC, with the widest latitudinal location of the EIA crests, and June solstice recorded the least, with the characteristic equatorward collapse of the EIA crests. TEC and the location of the crests of the EIA also increased with solar activity. TEC showed good correlations for conjugate pairs of stations, especially for stations closer to the trough. The African EIA morphology showed asymmetry in the locations of the Northern Hemisphere (NH) and Southern Hemisphere (SH) crests. The formation of EIA starts around 0600–0800 LT and decays around 2100–2300 LT. Generally, SH crest forms first before NH crest and also decays first; we attributed this to the effects of the meridional neutral winds. Comparing TEC at African EIA crests with other longitudinal sectors, the Asian sector recorded the highest TEC, while the American sector recorded the least. Key Points: The formation of the African EIA starts first in the Southern Hemisphere crest (0600–0800 LT) and decays first in the same hemisphere (2100–2300 LT) Station‐to‐trough ratio (STR) is characterized by two remarkable peaks at stations around the EIA crests Total electron content (TEC) measurements at conjugate pairs of stations showed reasonable correlations